Extraction and purification of proteoglycans from mature bovine bone. - Franzén, A (1984)
Proteoglycans were extracted in good yields from the mineralized matrix of ground bovine bone, by using a two-step extraction procedure. Proteoglycans (8% of total), not associated with the bone mineral, were extracted at - 20 degrees C with 4M-guanidinium chloride containing proteinase inhibitors. Proteoglycans associated with the mineral, which accounted for 60% of the total, were then solubilized when EDTA was added to the extraction solvent. They were fractionated and purified in the presence of 4M-guanidinium chloride by CsCl-density-gradient centrifugations followed by chromatography on Sepharose CL-4B. Further purification was obtained by chromatography on DEAE-cellulose and hydroxyapatite in the presence of 7 M-urea. Three populations of proteoglycans and additional glycosaminoglycan peptides were obtained. The molecular dimensions of both intact molecules and of their side chains as well as their amino acid composition were different, indicating that they represent separate molecular entities. The main proteoglycan self-aggregated in the absence of 4M-guanidinium chloride or 7 M-urea, a property that was abolished when the proteoglycan core protein was fragmented.